Radiative stabilization of C6−. (August 2015) - Chandrasekaran, V; Kafle, B; Prabhakaran, A; Heber, O; Rappaport, M L; Rubinstein, H; Schwalm, D; Toker, Y; Zajfman, D
Synopsis: Absolute rate coefficients were determined for the recurrent fluorescence (RF) process in C6 − anions at excitation energies above the adiabatic electron attachment energy. The RF process is an important ingredient in understanding the formation and stabilization of anions in the interstellar medium.